Art, communication, technologies - Barbero, Jesús Martín (Estudios de Filosofía, 1996)
The debate aboutt he "end of art" or about the end of the XX century is involved in the contradictions of a modernity spotted of premodem components. This dualism has led to a cultural disarrangement which is evident in the hybrid composition of society. lt is manifested also in the trials made to understand how the social dilferences and the elements of inclusion or exclusion according to which what is popular or cultivated and what is massifare distinguished, were built up. This cultural disarrangement can be seen close relationship between the ways of symbolizing and ritualizing the social link, and the communications net and the audiovisual flow.